Prevalence of Genotypes and Subtypes of Gardnerella vaginalis in South African Pregnant Women - Kayla Pillay; Silondiwe Nzimande; Meleshni Naicker; Veron Ramsuran; Partson Tinarwo; Nathlee Abbai (Hindawi Limited, 2020)
Background. Gardnerella vaginalis, a microorganism highly linked to bacterial vaginosis (BV), is understudied in terms of genotypic heterogeneity in South African populations. This study investigated the prevalence of G. vaginalis genotypes in BV-positive, BV-intermediate, and BV-negative South African pregnant women. Methods. The study population included n=354 pregnant women recruited from a public hospital in Durban, South Africa. The women provided self-collected vaginal swabs for BV diagnosis by Nugent scoring. For the genotyping assays, the 16S rRNA and sialidase A genes from BV-negative, BV-intermediate, and BV-positive samples were amplified with G. vaginalis-specific primers. The16S rRNA amplicon was digested with TaqI to generate genotyping profiles, and subtypes were determined by correlating BamHI and HindIII digestion profiles. Phylogenetic analysis was performed on the 16S rRNA and sialidase A sequences. The data analysis was performed with R Statistical Computing software, version 3.6.2. Results. Two different genotypes, GT1 and GT2, were detected. The most prevalent genotype was GT1. Four subtypes (1, 2B, 2AB, and 2C) were shown to be present. The most prevalent subtype was 2B, followed by subtypes 1, 2C, and 2AB. The phylogenetic analysis of the 16S rRNA showed the presence of 5 clusters. The tree displayed clusters which contained sequences from the same BV group with different genotypes and subtypes. Clusters with sequences from across the BV groups carrying the same genotype and subtype were present. Diversity of the sialidase A across BV groups and genotypes was observed. Finally, the study did not find a significant association (p>0.05) between reported symptoms of abnormal vaginal discharge and genotype harboured. Conclusion. This study provided the first report on the diversity of G. vaginalis in South African pregnant women. Diversity assessments of G. vaginalis with respect to genotypes and virulence factors may aid in a greater understanding of the pathogenesis of this microorganism.